P215 The incremental disease burden associated with the persistence of morning, daytime and night-time symptoms in chronic obstructive pulmonary disease patients. (15th November 2016) - Munoz, A; Bailey, J; Wood, R; Ribera, A; Nuevo, J
Abstract : Introduction: The current Global Initiative for Chronic Obstructive Lung Disease Strategy makes limited references to the variability of chronic obstructive pulmonary disease (COPD) symptoms according to the time of day patients experience symptoms, on awakening/morning, in the daytime and at night-time; therefore it's unclear whether specific treatment approaches are needed. Aims: To establish the association between time of day of symptoms and the burden experienced by patients; as measured by validated patient-reported outcomes (PROs), healthcare resource utilisation (HRU) and physician-perceived impact of COPD on patients' lives. Methods: Data were taken from four waves (2012–2016) of the Respiratory Disease Specific Programme (DSP); cross-sectional surveys of COPD patients in France, Germany, Italy, Spain, and the UK. Patients were defined as suffering from symptoms on awakening/morning (M), in the daytime (D), at night-time (N) or combinations of these according to physician-reported time of day of symptoms within the last 4 weeks. Kruskal-Wallis tests assessed statistical significance of outcomes across patient groups. Outcomes included HRU in the last 12 months, EQ-5D-3L with visual analogue scale, Jenkins Sleep Evaluation Questionnaire, COPD Assessment Test, activity impairment (measured by the work productivity and activity impairment questionnaire), and physician-reported impact COPD has on the patient's sleep. Results: In total, 8185 patients receiving treatment were analysed; 25% suffered no symptoms, 16% D only, 17% M/D only, 6% D/N only, 4% M, N or M/N only and 32% M/D/N. Across the four DSP waves, patients suffering any M, D or N symptoms ranged from 46%−64%, 67%–77% and 38%–47%, respectively. All outcomes differed significantly across patient groups (Table 1 ). In general, M/D/N patients utilised the most healthcare resources, suffered more exacerbations requiring emergency room visits or hospital admissions, had higher activity impairment and reported worse quality of life and sleep, whilst asymptomatic patients utilised the least resources and reported the best quality of life and sleep. The remaining groups suffered similar levels of burden. Conclusions: In this analysis, patients experiencing morning, daytime and night-time symptoms have the worst PROs and more disease burden. Clearer recognition of symptom burden and an individualised treatment approach may be warranted for these patients.